2009
DOI: 10.1128/jb.01616-08
|View full text |Cite
|
Sign up to set email alerts
|

Copper Acquisition Is Mediated by YcnJ and Regulated by YcnK and CsoR in Bacillus subtilis

Abstract: Copper is an essential cofactor for many enzymes, and at over a threshold level, it is toxic for all organisms. To understand the mechanisms underlying copper homeostasis of the gram-positive bacterium Bacillus subtilis, we have performed microarray studies under copper-limiting conditions. These studies revealed that the ycnJ gene encodes a protein that plays an important role in copper metabolism, as it shows a significant, eightfold upregulation under copper-limiting conditions and its disruption causes a g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
102
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(104 citation statements)
references
References 37 publications
2
102
0
Order By: Relevance
“…A role for these proteins in Cu(I) storage is currently the most logical suggestion for their function, but in many cases what they are storing Cu for remains unknown. The presence of bacterial Cu storage proteins seems consistent with a number of other observations: (1) that bacterial Cu-import systems exist (6,7,17,21,52,56,77,95), including into the cytosol; (2) that endogenous pools of the metal are available in bacteria (11,15,16,18,96); and (3) that E. coli grown in both LB and minimal medium accumulates Cu (97). It also highlights that there are alternative mechanisms to using different cellular compartments to prevent mis-metallation of proteins by Cu (37).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…A role for these proteins in Cu(I) storage is currently the most logical suggestion for their function, but in many cases what they are storing Cu for remains unknown. The presence of bacterial Cu storage proteins seems consistent with a number of other observations: (1) that bacterial Cu-import systems exist (6,7,17,21,52,56,77,95), including into the cytosol; (2) that endogenous pools of the metal are available in bacteria (11,15,16,18,96); and (3) that E. coli grown in both LB and minimal medium accumulates Cu (97). It also highlights that there are alternative mechanisms to using different cellular compartments to prevent mis-metallation of proteins by Cu (37).…”
Section: Discussionsupporting
confidence: 70%
“…Copper homeostasis has been extensively investigated in certain Csp3-possessing non-methanotrophs, with probably the best example being Bacillus subtilis (21,28,68,76,77). Therefore, the Csp3 from this model Gram positive bacterium has been studied in vitro (36).…”
Section: Csp Homologues In Non-methanotrophsmentioning
confidence: 99%
“…Moreover, the ycnJ transcript increased greatly under copper limitation. 77) These findings indicated that the primary role of B. subtilis YcnJ is associated with copper uptake.…”
mentioning
confidence: 70%
“…75) The B. subtilis YcnJ protein was found as a homolog of P. syringae CopCD; CopC and CopD are considered to be a periplasmic copper-binding protein and an inner membrane protein, respectively, and the N-and C-terminal parts of YcnJ show high homology to CopC and CopD. [75][76][77] It was demonstrated that copCD expression in a P. syringae host, which does not have copper resistance, causes copper hypersensitivity and hyperaccumulation, suggesting that CopCD is also capable of copper uptake. 76) In B. subtilis, disruption of ycnJ resulted in a growth-defective phenotype under copper limitation and a reduced intracellular copper content.…”
mentioning
confidence: 99%
“…YcnI is a protein that is speculated to be involving in copper acquisition and it is important during copper limiting conditions [15]. CopA/B is a type of protein that convey copper ions across cell surface and intracellular membrane [16], Cop C/D are the soluble periplasmic chaperone that bind to Cu(I) and Cu(II), they are hypothesized to be the transporter of All rights reserved.…”
Section: Copper Homeostasis Genes Of B Thuringiensismentioning
confidence: 99%